A systematic field effectiveness evaluation of three maintenance measures for three permeable pavements. (17th October 2022) - Wu, Yunhong; Li, Junqi; Zhang, Xiaoran; Lin, Cong; Guo, Xiaopeng; Zhang, Xingyu
Graphical abstract: Highlights: The optimal maintenance times for each permeable pavement were 2–3 times. The optimal maintenance period was related to the stable permeability ratio. The optimal maintenance measure was evaluated by efficiency, cost, energy. Characteristic sediment particle enhanced clogging and weakened maintenance. Abstract: Various maintenance measures have been used to better maintain permeable pavements. However, for a certain permeable pavement, the effects of the maintenance measures, maintenance times, maintenance period, and sediment particle size on the maintenance efficiency are not clear. In this study, in order to explore the above issues, high-pressure water washing (HW), low-pressure suction (LS), and high-pressure air flushing (HA) were applied on pervious concrete pavement (PC), interlocking impermeable concrete brick pavement (IIC) and interlocking permeable concrete brick pavement (IPC), then the maintenance efficiencies under different maintenance conditions were compared. The result showed that the optimal maintenance times of the three maintenance measures were 2–3 times. The optimal maintenance period for periodic maintenance could be determined by the initial permeability and stable permeability ratios at different initial clogging ratios, while the clogging ratio could be used as a maintenance indicator for non-periodic maintenance. The sediment particle size (0.3–1.16 mm) causing the most serious clogging was 1–2 times the permeable pavement characteristic aperture which was related to the distribution of pavement pore area and number over the pore size. The optimal maintenance measures of PC, IIC, IPC were LS, HW, and LW respectively, based on a comprehensive evaluation using three indicators: maintenance efficiency, maintenance cost, and energy consumption. This study provides an important reference for selecting appropriate maintenance measures and the characteristic aperture of permeable pavement according to local conditions.